How Does the Electronic Products Retailer Transform Operational Modes Considering Consumer Preferences for Leasing?. (20th September 2022) - Tian, Gaidi; Li, Chunfa; Li, Dongdong
Abstract : Consumer interest in renting brand-new electronic products has increased recently. Some retailers started to lease them, but they remarkably depreciate shortly after leasing. If their rental income cannot bring in enough profit, should a retailer lease them? This paper uses consumer preferences for leasing to describe their rental utility. It develops an analytical framework to study how the retailer selects operational modes. In a supply chain consisting of a manufacturer and a retailer, three different operational modes are analyzed: pure selling (S), pure leasing (L), and hybrid selling-leasing (SL). Results mainly show that when consumer preferences for leasing exceed a certain threshold, both the manufacturer's and the retailer's profits can be increased if the retailer transforms the business operational mode from S to SL/L. When consumer preferences for leasing are within a certain range, the retailer's profits can be increased if the operational mode is transformed from S/L to SL. This happens as both consumers' lease and purchase requirements for electronic products are met after the transformation. The wholesale price, leasing price, selling price, and the manufacturer's profit all rise in the SL mode as consumer preference for leasing rises, but the retailer's profit falls. Only if the retailer cooperates with the manufacturer can the operational mode be transformed from S/L to SL when consumer preferences for leasing are lower, and the coordination contract can achieve Pareto improvement in the profits of both the manufacturer and the retailer.